PEMANFAATAN ARTIFICIAL INTELLIGENCE DALAM PEMBELAJARAN DASAR: HASIL PENGABDIAN DI MI PLUS AL-FATIMAH BOJONEGORO - Ita Aristia Sa’ida; Guruh Putro Dirgantoro; Dwi Issadari Hastuti; Niken Sukmawati; Elsa Azia Ulhaq (Bajang Institute, 2025)
The rapid development of Artificial Intelligence (AI) offers significant opportunities to enhance the quality of learning, particularly at the elementary and madrasah levels. However, teachers’limited digital literacy and lack of experience in utilizing AI-based tools often hinder the integration of technology into classroom practices. This community service program aims to strengthen teachers’ competencies in implementing AI to support teaching and learning at MI Plus Al-Fatimah, Bojonegoro. The program was conducted through four stages: socialization, training, classroom implementation with mentoring, and evaluation. Various AI-based teaching products were produced, including digital learning materials, interactive assessments, infographics, and instructional videos. Evaluation results show a substantial improvement in teachers’ digital literacy and confidence, with an average increase of 65% between pre-test and post-test scores. Teachers reported that AI tools improved efficiency in preparing teaching materials, enhanced classroom engagement, and helped diversify instructional strategies. This program demonstrates that AI integration can serve as an effective capacity-building mechanism for teachers, promoting innovative, adaptive, and technology-driven learning environments. The findings suggest that continuous training, infrastructural support, and clear implementation guidelines are necessary to sustain AI adoption in schools and broaden its impact across educational settings.